Management of elderly patients with unresectable pancreatic cancer - Kobayashi, Satoshi; Ueno, Makoto; Ishii, Hiroshi; Furuse, Junji (Japanese journal of clinical oncology, 2022)
Systemic chemotherapy plays important role in pancreatic cancer not only for palliative treatment of unresectable disease, but also for neoadjuvant and adjuvant treatment of resectable disease. Most clinical trials of systemic chemotherapy have been conducted in non-elderly patients, and the results cannot always be extrapolated to elderly patients because of the uniqueness of this population. The number of elderly patients with pancreatic cancer has increased in an aging society; therefore, there is an urgent need to develop specific treatments for elderly patients with pancreatic cancer. Gemcitabine or S-1 monotherapy is generally considered appropriate even for vulnerable elderly patients. FOLFIRINOX is considered inapplicable based on its safety profile. Gemcitabine plus nab-paclitaxel and nanoliposomal irinotecan with fluorouracil plus folinic acid can be administered to elderly patients, because the phase III trials have shown the efficacy and safety for patients including those who were 75 years or older. However, the feasibility of these therapies for elderly patients is still under debate since the number of elderly populations was relatively small in these studies. To determine the indication for these regimens in the elderly, the background of each patient should be considered. Geriatric assessment such as the Geriatric 8 and the Geriatric Nutritional Risk Index can identify vulnerabilities and are therefore recommended in daily clinical practice as well as in clinical studies of elderly patients. It is expected that geriatric assessment will elucidate the eligibility criteria for those regimens in elderly individuals. Randomized clinical trials are ongoing to establish a standard treatment in the vulnerable elderly with advanced pancreatic cancer, who cannot tolerate the same regimen as in the non-elderly patients.